Student Narrative Against Hoax News on Social Media - Mukoyimah Mukoyimah (Faculty of Ushuluddin and Dakwah, UIN K.H. Abdurrahman Wahid Pekalongan, Central Java, Indonesia, 2021)
Being a student in this era of digitalization and the increasingly sophisticated world of telecommunication, presents its own challenges. that's why the author conducted research with the aim of digging deeper into student involvement in the digital era through social media in countering hoax news. The author in this study used the Forum Group Discussion method, which was carried out separately in two groups, namely students and college students. Segregated by gender because to minimize the swaying of opinion. The FGD was conducted on 10 students from four faculties. The data is processed using the Miles Huberman and Saldana data collection, condensation, and presentation models. Meanwhile, to review the validity of the data, the author uses a data triangulation model. The results of the author's research show that 60% of students are classified as very active on social media with an accuracy of 70% of student activities in verifying information on social media. The form of counter-narratives that students do is the first active clarification in their social media channels. Second, students make correct narrations as a form of contradiction to the content of the untrue news that has spread. Third, if students have not been able to make a correct narrative, students prefer not to spread / stop the chain of sharing hoax news in the community.